The Effect of Hot Band Annealing and Cooling on the Microstructure of 3.2% Si NonOriented Electrical Steels - CALLUM JONES (2024)
This project investigated the effect of the hot band annealing process on the properties of 3.2 wt.% Si non-grain oriented electrical steels with compositions at the extremes of the specification range (between 3.2 and 3.5 wt.% Si). Electron backscatter diffraction was used to characterise both microstructure and texture. A general examination of industrial hot band and hot band annealed samples found an inhomogeneous microstructure and texture distribution through the cross section of the hot band and often incomplete recrystallization in the annealed state. Persistent pancake shaped grains were found to have recovered dynamically during hot rolling which prevented recrystallization from occurring during the subsequent annealing, independent of texture. Slow cooling rates from the annealing temperature of 940 ˚C to less than 50 ˚C were found to complete recrystallization in samples where persistent 훼 − 푓푖푏푟푒 grains were previously present whilst the less prevalent {110}〈001〉 Goss grains would remain. Increasing the annealing temperature from 940 ˚C to 960 ˚C whilst keeping the heating rate constant and varying the cooling rate, resulted in a similar recrystallization outcome with an undesirable excessively large grain size. Finally, a quasi in-situ experiment to track the recrystallization process during annealing found an onset of recrystallization at 930 ˚C. A relationship was found between deformed regions of certain texture recrystallizing into specific orientations. The large stubborn grains were found to be slowly consumed by neighbouring grains through a process termed ‘bulging’. This developed new knowledge has led to recommendations for the optimum hot band annealing cycle to be applied at the industrial sponsor together with greater understanding of the mechanism for the evolution of extreme brittleness caused by large grains in some 3.2 wt.% silicon hot band annealed coils.